Obtenção de um filme fino de FTO pela técnica de spray-pirólise e método sol-gel para utilização em células solares orgânicas - Maia Júnior, Paulo Herbert França (2015)
The growing interest in the use of new materials and their applications for photovoltaic systems has been a constant concern of the scientific community in recent years. This work is primarily engaged in the collection, characterization and photoactivity testing photovoltaic solar cells made of thin SnO2 doped fluoride films, the films were deposited by the technique of "spray-pyrolysis" and the Sol-Gel method in substrate glass. In glasses microscopy work with dimensions of 2.5 x 7.5 x 1 mm are used as matrices for the conductive substrates or transparent conductive oxides (TCO). These glasses have electrical resistance and transmittance adequate for the manufacture of photoelectrochemical solar cells activated by dyes. Besides making the glasses must be made conductive depositing a layer of titanium oxide, preparation of electrolyte, dye, assembly and characterization of the cells. The conductive substrate has a film of tin dioxide doped with fluorine (SnO2: F), the deposition is made with the aid of a compressor and a spray gun on the glass at a temperature of 600° C from a solution made by the method Sol- gel (MSG). As characterization techniques were used: x-ray diffraction (EDX), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), UV-Vis and Van der Pauw method. The conductive glass has transmittance of 80% (400 nm - 800 nm). The cell with mesoporphyrin dye has Vac = 0.34V and Icc ~ 150μA. The experimental results obtained from these cells may contribute to the development of prototypes that can be used commercially in the capture of solar energy and its consequent transformation into electricity.